Formation of the Patagonian Orocline and paleogeographic evolution of the Patagonian –Antarctic Peninsula System - Poblete, Fernando (HAL CCSD, 2015)
At the continental scale, the Andes presents significant curvatures. One of the largest is the curvature of Patagonia, where the orogen and its main tectonic provinces are rotated about 90 ° from an NS direction at 50 ° to an EO orientation in Tierra del Fuego. Despite its importance, the origin of the curvature of Patagonia and its involvement in paleogeographic reconstructions remain controversial: is the result of an oroclinal bending, or an inherited characteristic? It is in this context that I made a paleomagnetic and magnetic susceptibility anisotropy in the Austral Andes region. The results suggest that the inner part of the bend is a secondary feature linked to the evolution of the Antarctic Peninsula.In this thesis, I will present the results of a paleomagnetic and anisotropy of magnetic susceptibility (AMS) study of 146 sites sampled between 50 ° S and 55.5 ° S (85 sites in marine sedimentary rocks of the Cretaceous-Miocene of the Magallanes fold and thrust belt; 20 sites in sedimentary and volcanic rocks south of Cordillera Darwin, 41 sites in intrusive rocks of the Cretaceous-Eocene batholith. The AMS results in the sediments show that the magnetic fabric is controlled by tectonic processes, partially or completely obliterating the sedimentary fabric. In general, there is a good correlation between the orientation of the magnetic lineation and that of the fold axes except at Peninsula Brunswick. The wide variation in the orientation of magnetic fabrics within the batholith suggests an emplacement of intrusive without tectonic constraint. Paleomagnetic results obtained in Navarino Island and Hardy Peninsula, south of the Beagle Channel, show a post-tectonic remagnetization recording a counterclockwise rotation of more than 90 ° as that recorded by the intrusive rocks older than ~ 90Ma. The Upper Cretaceous to Eocene intrusive rocks record counterclockwise rotations of lower magnitude (45 ° -30 °). In contrast, the Magallanes fold and thrust belt mainly developed between the Eocene and Oligocene ...